Parks and people : managing outdoor recreation at Acadia National Park - Manning, Robert E., 1946- (University of Vermont Press ; University Press of New England, 2009)
A science-based approach to outdoor recreation management at Maine's Acadia National Park, applicable to parks and conservation areas nationwide.